Relationship between Related Party Transactions and Earnings Management - Narges Sarlak; Mina Akbari (بررسی‌های حسابداری و حسابرسی, 2014)
This study uses data from companies listed on the TehranStock Exchange to investigate whether related party transactions areassociated with earnings management. According to the agency theorybecause of the separation of ownership from control, conflict ofinterest may arise, so if a firm`s executives and/or board membersengage in related party transactions to expropriate the firm`sresources, then they have incentives to manage earnings to mask suchexpropriation. The research uses the related party transactions as theindependent variable and discretionary accruals as the dependentvariable. The sample of study includes 145 companies from 2008 to2012. The panel data and multiple linear regressions are used toexamine the hypothesis. The results of this study reveal that there is asignificant positive relationship between the related party transactionsand earnings management.